Characterization of an Expectorant Herbal Basak Tea Prepared with Adhatoda vasica Leaves - Sarker, Ashish K; Ahamed, Kabir; Chowdhury, Jasim Uddin; Begum, Jarifa (Bangladesh Journal of Scientific and Industrial Research, 2009)
A herbal tea for an expectorant action was prepared with Adhatoda vasica leaves. Analytical, pharmacological, microbiological and animal toxicity studies were carried out to characterize the herbal tea. The analytical data indicates that the alcohol extract from herbal basak tea contains 0.67% crude alkaloids and the isolated tracheal chain experiment with this extract showed small relaxation effect compare to the standard histamine drug. The crude alkaloids and the other extracts (petroleum ether extract, alcohol extract and hot water extract) showed mild inhibition in different degrees against different microorganisms. The animal toxicity studies on rats revealed no mortality after 24 hours and also no abnormal delayed effect indicates no toxicity of prepared tea at all. Based on the above results, the prepared herbal basak tea is proposed as a good expectorant. Herbal tea prepared with Adhatoda vasica leaves collected in May to September showed better efficacy than those of other times. Key words: Herbal basak tea, Crude alkaloids, Relaxation effect. DOI: 10.3329/bjsir.v44i2.3674 Bangladesh J. Sci. Ind. Res. 44(2), 211-214, 2009